2023
DOI: 10.32744/pse.2023.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The image of academic dishonesty through the eyes of students: an analysis of videos

Abstract: Introduction. Academic dishonesty impedes the achievement of the goals of education, depriving the meaning of the procedure for monitoring the knowledge and skills of students. The purpose of the article is to identify the place of cheating in the life of a student, its features and specifics. Materials and methods. The study involved 225 1-2 year students of Peter the Great St. Petersburg Polytechnic University who created their own videos on academic dishonesty. Research methods: semiotic and pedagogical-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Research has shown that online academic dishonesty differs significantly from traditional forms, with online students engaging in behaviors like copying digital work, imitating technical issues, and googling for answers [ 1 ]. Furthermore, academic dishonesty is often viewed as a social norm, with students demonstrating a readiness to cheat and even opposing teachers in an organized manner [ 2 ]. Cognitive and emotional factors play a role in students' decisions to support academic integrity standards, especially in the face of electronic deception, which has become more widespread with the rise of distance learning and online education [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that online academic dishonesty differs significantly from traditional forms, with online students engaging in behaviors like copying digital work, imitating technical issues, and googling for answers [ 1 ]. Furthermore, academic dishonesty is often viewed as a social norm, with students demonstrating a readiness to cheat and even opposing teachers in an organized manner [ 2 ]. Cognitive and emotional factors play a role in students' decisions to support academic integrity standards, especially in the face of electronic deception, which has become more widespread with the rise of distance learning and online education [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that EFL students are engaged in plagiarism due to three factors [ 1 ]: convenient access to online resources enabled EFL students to retrieve information without properly citing the sources [ 2 ], questionable teacher assessment, and [ 3 ] students' poor academic writing skills [ 38 ]. Cheating among college students is influenced by factors such as moderate expectations of success, past cheating experiences, and positive attitudes toward cheating.…”
Section: Introductionmentioning
confidence: 99%